The DNA damage response - Costanzo, Vincenzo (Henry Stewart Talks, 2009)
Genomic instability in cancer, DNA structure checkpoint, ATM, ATR and related proteins, Xenopus laevis egg extract as a model system, Sensing the DNA break, Mre11/Rad50/Nbs1 complex, Sensing DNA double strand breaks: current model, ATM activation by ssDNA molecules, ssDNA oligo generation is MRN dependent, ATM, ATR and Mre11 complex deficiency in vertebrates, DNA structure checkpoint and mitotic catastrophe in vertebrates, ATM/ATR targets in mitosis after DNA damage, Centrosome as a target of DNA damage response